PENGARUH GOOD CORPORATE GOVERNANCE DAN KUALITAS AUDIT TERHADAP MANAJAMEN LABA - Dinda Azhari Faisal (2022)
The Influence of Good Corporate Governance and Audit Quality on Earnings Management By Dinda Azhari Faisal Abstract This study is a quantitative study with the aim of knowing and analyzing the effect of Good Corporate Governance as measured by the mechanism of an independent board of commissioners, audit committees, managerial ownership, and institutional ownership, as well as audit quality on earnings management in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2017 period. 2020. Using multiple linear regression and secondary data on 55 companies. This study detects earnings management by adopting the model of Yoon et al. (2006), the independent board of commissioners is based on the proportion of independent commissioners from the entire board of commissioners, the audit committee is based on the proportion of the audit committee with accounting and financial education background from the entire audit committee, managerial ownership is based on the percentage of managerial share ownership of outstanding shares, institutional ownership is based on the percentage of share ownership institutions of outstanding shares, and audit quality based on the size of the KAP. The results found are independent commissioners, audit committees, managerial ownership, institutional ownership, and audit quality have no significant effect on earnings management. Keywords: Independent board of commissioners, Audit Committee, Managerial and Institutional Ownership, Audit Quality, Earnings management.